Patent Citations and the Geography of Knowledge Spillovers: A Reassessment: Comment - Henderson, Rebecca; Jaffe, Adam; Trajtenberg, Manuel (American Economic Review, 2005)
Patent Citations and the Geography of Knowledge Spillovers: A Reassessment: Comment by Rebecca Henderson, Adam Jaffe and Manuel Trajtenberg. Published in volume 95, issue 1, pages 461-464 of American Economic Review, March 2005